The effects of underwriters on the flotation costs of SEOs and the likelihood of investor participation in equity offerings - Kong, Zeyu (2015)
Underwriting is a key factor in equity offerings and many scholars have sought to shed light on the role that underwriters play in the investment banking industry. My thesis extends existing studies by investigating how underwriters affect the flotation costs of SEOs and the likelihood of investor participation in equity offerings.